REPRESENTAÇÕES SOCIAIS SOBRE A EDUCAÇÃO INFANTIL AS VOZES DAS PROFESSORAS - Costa, Cleusa Vieira da (2009)
This study indentifies the social representation of teachers of the firsts levels of child education and of the first period of elementary education about the subject of the child education. Based on Moscovici’s (1978) and Jodelet’s (2004) reflections, in view of the Theory of Social epresentations, the reflection is focused in the participants speeches. They are social representations that are “forged” in the group, and they show the understanding of its members about the reality. The speeches presented by the teachers were analyzed by Alceste software and also by Evoc program. The data-processing enabled us recognize the space of the child education as a dynamic universe of knowledge and construction (growth). The social representations presented by the teachers through this research show us a speech formed historically by the group and strongly marked by its theoretical formation. Following the historical process in wich the child education has been managed, we verified some trends that mark the teachers speech today. When comparing the speaking of these subjects, we verify that their theoretical references, their educational trajectory and the social history of the child education are preponderant factors for the formation of them consensual universe and, consequently, of them social representations. The teachers speeches confirm that the history, the experience in the group and the theories wich embased their formation contribute to the construction of the social representations. Thus, the representations unravel taht the teachers think about the child education as the propitious place for the whole development of the child, interspersed by playful pedagogical activities, seeking for the formation of the citizen and his inclusion in the school universe. The child education is anchored on the Idea of development and the teachers objectify this representation by the figure of the tree wich grows, the se ds that germinate, or the stairs that take us to the upper stages. When talking to the teachers, we have understood that the social representations are present in their everyday life and they compose their practical: speeches and gestures give the content to their world.(AU)